Targeting human telomeric G-quadruplex DNA with curcumin and its synthesized analogues under molecular crowding conditions. Issue 9 (19th January 2016) - Jha, Niki S.; Mishra, Satyendra; Mamidi, Ashalatha S.; Mishra, Archita; Jha, Shailendra K.; Surolia, Avadhesha
Abstract : The formation of telomeric G-quadruplexes has been shown to inhibit telomerase activity. Abstract : The formation of telomeric G-quadruplexes has been shown to inhibit telomerase activity. Indeed, a number of small molecules capable of π-stacking with G-tetrads have shown the ability to inhibit telomerase activity through the stabilization of G-quadruplexes. Curcumin displays a wide spectrum of medicinal properties ranging from anti-bacterial, anti-viral, anti-protozoal, anti-fungal and anti-inflammatory to anti-cancer activity. We have investigated the interactions of curcumin and its structural analogues with the human telomeric sequence AG3 (T2 AG3 )3 under molecular crowding conditions. Experimental studies indicated the existence of a AG3 (T2 AG3 )3 /curcumin complex with binding affinity of 0.72 × 10 6 M −1 under molecular crowding conditions. The results from UV-visible absorption spectroscopy, a fluorescent TO displacement assay, circular dichroism and molecular docking studies, imply that curcumin and their analogues interact with G-quadruplex DNA via groove binding. While other analogs of curcumin studied here bind to G-quadruplexes in a qualitatively similar manner their affinities are relatively lower in comparison to curcumin. The Knoevenagel condensate, a methoxy-benzylidene derivative of curcumin, also exhibited significant binding to G-quadruplex DNA, although with two times decreased affinity. Our study establishes the potential of curcumin as a promising natural product for G-quadruplex specific ligands.